2021
DOI: 10.5812/aapm.112592
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Versus Phonophoresis Therapy for Neck Myofascial Pain Syndrome: A Randomized Clinical Trial

Abstract: Objectives: This study aimed to assess the effects of using Extracorporeal Shock Wave Therapy (ECSWT) and phonophoresis therapy on pain and neck disability in patients with neck myofascial pain syndrome (MPS). Methods: Forty eligible patients were randomly divided into two groups of ECSWT (received three sessions of ECSWT, once a week for three weeks) and phonophoresis (received ultrasound using hydrocortisone gel 1% over the trigger point on trapezius muscle, three times a week for three weeks). Patients in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…This result agreed with Taheri et al (2021), their results indicated significant improvement on pain intensity and neck disability immediately and after four weeks of intervention. After the treatment, the pain score in the rESWT group was significantly lower than in the phonophoresis group.…”
Section: Discussionsupporting
confidence: 89%
“…This result agreed with Taheri et al (2021), their results indicated significant improvement on pain intensity and neck disability immediately and after four weeks of intervention. After the treatment, the pain score in the rESWT group was significantly lower than in the phonophoresis group.…”
Section: Discussionsupporting
confidence: 89%
“…There are several alternatives to corticosteroids administration. One of them is phonophoresis, this being an effective and painless method of administration [ 7 ]. It is applied by using the cavitation effect produced by an ultrasonic wave allowing drug penetration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the studies on ESWT for MTrPs of the UTM published so far [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] did not show any advantage of focused ESWT (fESWT) over rESWT or vice versa (a detailed discussion of differences between and similarities of fESWT and rESWT is provided in [56]). This is important because the use of fESWT is restricted to physicians in many countries (as is the case in Germany where chiropractors and physiotherapists who have been trained in Germany are not legally entitled to use fESWT).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, extracorporeal shock wave therapy (ESWT) has emerged as an effective and safe alternative for treating MTrPs [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. According to a recent systematic review and meta-analysis, ESWT appears to be associated with higher pain alleviation than sham ESWT or ultrasound therapy in treatment of MTrPs in the UTM [38].…”
Section: Introductionmentioning
confidence: 99%